Urban Land and Housing Markets in the Punjab, Pakistan - World Bank (Washington, DC, 2012)
This note provides a short overview of urban land and housing market performance in Punjab Province of Pakistan. It describes the characteristics of well-functioning urban land and housing markets and argues that, at present, the Punjab's urban land and housing markets are not performing well. The paper identifies a range of structural and institutional shortcomings that impede urban land market performance, and then concludes by offering recommendations for making land and housing markets functions better. The Punjab Province in Pakistan is in the midst of a profound urban transition, driven by structural economic change. The Punjab is transforming from an agriculturally-based economy to a manufacturing and service based economy, which is leading to massive urbanization. This background paper reviews and assesses how well the Punjab's urban land and housing markets are functioning. The evidence suggests that urban land and housing markets are not performing as well as they could. Urban land-use planning and development controls are impeding urban development, while land titling and registration systems hamper real estate development. Systems of local resource mobilization and taxation do not generate sufficient revenues to fund key urban infrastructure. The paper notes the several critical negative consequences of poor urban land market performance, namely high land and housing prices, large and expanding katchi abadi developments, poorly located industrial estates, inadequate urban infrastructure, and constrained commercial development.